2022
DOI: 10.1101/2022.06.10.495696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fitness seascapes are necessary for realistic modeling of the evolutionary response to drug therapy

Abstract: Predicting the evolution of drug resistance in infectious diseases may enable us to make rational drug choices to avoid resistance and exploit known molecular mechanisms of resistance. Fitness landscapes are commonly used in computational studies to model the genotype-fitness mapping. Canonical fitness landscapes do not intrinsically model varying selection pressure. However, a challenge to predicting the emergence of drug resistance is that disease agents in a patient will never experience a constant environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Dose response curves differ in their IC 50 and drug-free growth rates. Empirical fitness seascapes bearing a similar structure and demonstrating fitness tradeoffs have been reported by others 7, 19, 25 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Dose response curves differ in their IC 50 and drug-free growth rates. Empirical fitness seascapes bearing a similar structure and demonstrating fitness tradeoffs have been reported by others 7, 19, 25 .…”
Section: Resultssupporting
confidence: 77%
“…Others have shown computationally and experimentally that drug diffusion gradients and differential drug penetration, which permit heterogeneous MSWs, facilitate antibiotic resistance 11, . Considering drug pharmacokinetics in time, Nande and Hill, among others, have shown that drug absorption rate and patient nonadherence can impact the evolution of resistance 12, 25 . Our results suggest that this is likely a function of both the time spent in the MSW and, in the case of nonadherence, the drug concentration dropping back down into a MSW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for their temporal variability (e.g. under the effect of treatment), then sometimes referring to them as fitness seascapes, has important consequences for the understanding of adaptation, such as resistance evolution (Lässig et al, 2017; King et al, 2022). For example, Hemez et al (2020) found in a simulation study that the drug mode of action (bacteriostatic vs. bactericidal) was changing the shape of the fitness landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Future work may seek to elaborate on these and other studies that highlight the role of environments in crafting plasticity and adaptive evolution [53][54][55]. Such efforts may include studies of "fitness seascapes" and evolution in fluctuating environments, as has been examined by others [56][57][58]. Like many others, we believe that we are only at the beginning of a larger, holistic effort to supplement existing metrics and concepts developed within clinical medicine, all towards more effective therapies that can improve outcomes at the bedside.…”
Section: Ideas Speculation and Future Directionsmentioning
confidence: 99%